2013
DOI: 10.1103/physrevd.88.036010
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram for charged scalars in a magnetic field at finite temperature

Abstract: We investigate the nature of the phase transition for charged scalars in the presence of a magnetic background for a theory with spontaneous symmetry breaking. We perform a careful treatment of the negative mass squared as a function of the order parameter and present a suitable method to obtain magnetic and thermal corrections up to ring order for the high temperature limit and the case where the magnetic field strength is larger than the absolute value of the square of the mass parameter. We show that for a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…2{qB)2k\ + ■ > 2 + k 2 + m2)3J (21) The sum and integrals in 7"^0 are perform ed by means of the M ellin sum m ation technique [23] with the result Figure 4 shows the Feynm an diagrams that contribute to this correction. We are interested in also com puting an effective value for this coupling, < 7eff, for v = 0, in the sam e m anner w e did for 2eff-The columns where F, represents the incoming momentum and mu d are the u-and d-quark masses, respectively.…”
Section: One-loop Thermomagnetic Couplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…2{qB)2k\ + ■ > 2 + k 2 + m2)3J (21) The sum and integrals in 7"^0 are perform ed by means of the M ellin sum m ation technique [23] with the result Figure 4 shows the Feynm an diagrams that contribute to this correction. We are interested in also com puting an effective value for this coupling, < 7eff, for v = 0, in the sam e m anner w e did for 2eff-The columns where F, represents the incoming momentum and mu d are the u-and d-quark masses, respectively.…”
Section: One-loop Thermomagnetic Couplingsmentioning
confidence: 99%
“…The explicit computation is carried out in the weak field limit, with the boson propagator given by Eq. (21) and the fermion propagator given by [24] SB(K,mf )…”
Section: One-loop Thermomagnetic Couplingsmentioning
confidence: 99%
“…Nevertheless, the critical temperature and the order of this phase transition were not found in [13]. There is another group of papers [23,24] where the authors suggested that such a gas can condense if one goes beyond the naive oneloop approximation and takes into account the infrared enhanced contribution of the so-called ring diagrams [2,3,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…We work with the hierarchy of scales where qB, m 2 i < T 2 . It is known that in order to properly implement this hierarchy [20] it is necessary to separate the contribution from the zero mode from the rest of the modes in Eq. (13).…”
mentioning
confidence: 99%